Studi Pemanfaatan Limbah Padat Industri Pengolahan Minyak Kelapa Sawit Spent Bleaching Earth sebagai Pengganti Agregat pada Campuran Beton - Dermawan, Denny; Ashari, Mochammad Luqman (Universitas Diponegoro, 2018)
Palm oil refinery factory has solid waste by product called Spent Bleaching Earth (SBE). SBE consists of some chemical compounds and one of them is SiO2 up to 83,05%. SiO2 or silica fume can cause silicosis if it is exposed to the atmosphere and frequently inhaled by the workers. On the other hand, SiO2 is one of the material composition of Portland cement. Thus, it is necessary to conduct a research about the utilization of SBE. as a concrete mixture. SBE is utilized as fine aggregate substitution by the composition of 0%, 10%, 20%, 30%, and 40% of the total amount of fine aggregate. The conducted tests are fineness modulus calculation, compressive strength, setting time, and TCLP. The method used for mix design is SNI 03-2834-2000 with f’c 28,5 MPa and slump 12 ± 2 cm. This research shows that concretes with SBE substitution which achieve the planned compressive strength are 10% SBE with 34,16 MPa and 20% SBE with 29,06 MPa. Based on the TCLP test, the concentration of heavy metal substances in 10% SBE are below the standard. Thus, it is scientifically proven to conclude that concrete with 10% SBE is technically proper and safe for the environment.